ANALISIS MANAJEMEN PENGENDALIAN PERSEDIAAN BAHAN BAKU DAGING BABI DENGAN METODE ECONOMIC ORDER QUANTITY (EOQ) PADA RM. COTO BOKE UNGKE POLO MANADO - Calvin Tiwow (Jurnal LPPM Bidang EkoSosBudKum (Ekonomi,Sosial,Budaya, dan Hukum), 2023)
Inventory management is an important thing to do in a company, especially in a manufacturing company. Good inventory management can help companies to achieve optimal profits. Not a few of every company that has not implemented good inventory management experiences problems in inventory management, for example the company experiences an excess of raw materials or a shortage of raw materials, the impact of this problem is that the company will definitely experience a loss. The purpose of this research is to find out what is the optimal amount of raw material inventory in a company using the EOQ method. This research is a type of descriptive research with quantitative analysis methods. Research data was collected through interviews and observation, as well as documentation. The results showed that with the EOQ method, RM. Coto Boke Ungke Polo has to order 372 Kg of raw materials in one order, with a total order frequency of 6 times in 1 year, compared to what the company does which is 48 times in 1 year, and can optimize the total cost of inventory from RP. 3,933,493 to Rp. 3,240,172.